Enhancing Students’ Mathematical Problem-Solving Ability Through The Problem Posing and Solving Learning Model Assisted by Heyzine - Ria Setiani Habbinnur Rizki; Wati Susilawati; T. Tutut Widiastuti A; Ika Puspitawati (Universitas Wiralodra, 2025)
The integration of problem posing and problem-solving learning facilitates problem situations that require students to actively engage in tackling non-routine mathematical challenges. However, some students are still not well-adapted to this type of problem-solving, making it potentially less effective when applied simultaneously. This study aims to analyze students’ mathematical problem-solving abilities through problem-posing and problem-solving learning assisted by Heyzine. This research employed a quasi-experimental method. The population consisted of eleventh-grade students from a senior high school in Bandung Regency, with classes XI D1, XI D2, and XI E1, each comprising 37 students selected through random sampling. The findings of this study include: (a) the design of the Jucama learning model was successfully implemented, resulting in a Heyzine-assisted student worksheet (LKPD) that met the criteria of being highly valid and suitable for use; (b) the implementation process of the Jucama learning activities assisted by Heyzine improved significantly and achieved a very good category; (c) there was a notable increase in problem-solving ability among students who received Heyzine-assisted Jucama learning compared to those who received Jucama learning without Heyzine.